Fundamental issues in defense training and simulation - Best, Christopher (Human factors in defence, 2013)
The emergence of new operational drivers such as asymmetric threats, urban operations, joint and coalition operations, and the widespread use of military communications and information technology networks has highlighted the importance of providing warfighters with the competencies required to act in a coordinated, adaptable fashion, and to make effective decisions in environments characterised by large amounts of sometimes ambiguous information.